Recruitment Crisis in the North Atlantic Treaty Organization: Demographic and Regional Dimensions - Andrusiak, M. V.; Borysenko, M. V.; Zolotov, A. V.; Rusetskyi, R. Yu. (Ukrainian Geographical Journal, 2025)
The sharpening of the recruitment crisis in the member states of NATO is considered in the article as a result of demographic changes in the world in the early 21st century. The consequences of the demographic transition have led to a significant decrease in the number of the cohort of young men and a reduction in the recruiting niche in all countries of the Euro-Atlantic integration. The author believes that demographic obstacles have influenced the economic and cultural factors that shape the recruiting policy.